2020
DOI: 10.1073/pnas.2006186117
|View full text |Cite
|
Sign up to set email alerts
|

Selective tumor antigen vaccine delivery to human CD169 + antigen-presenting cells using ganglioside-liposomes

Abstract: Priming of CD8+ T cells by dendritic cells (DCs) is crucial for the generation of effective antitumor immune responses. Here, we describe a liposomal vaccine carrier that delivers tumor antigens to human CD169/Siglec-1+ antigen-presenting cells using gangliosides as targeting ligands. Ganglioside-liposomes specifically bound to CD169 and were internalized by in vitro-generated monocyte-derived DCs (moDCs) and macrophages and by ex vivo-isolated splenic macrophages in a CD169-dependent manner. In blood, high-di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 82 publications
1
50
0
Order By: Relevance
“…In addition, a new subset of human DCs, characterized by the expression of Axl and Siglec-6 (AS DC), was also shown to express CD169 [46]. We recently demonstrated that ganglioside-containing liposomes can be used to selectively target and activate these human AS DCs in a CD169-dependent manner [47]. In this study, we have optimized targeting to human and murine cells and show that the liposomal incorporation of either 3 or 5 mol% GM3 led to strong and specific binding to CD169-expressing cells in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a new subset of human DCs, characterized by the expression of Axl and Siglec-6 (AS DC), was also shown to express CD169 [46]. We recently demonstrated that ganglioside-containing liposomes can be used to selectively target and activate these human AS DCs in a CD169-dependent manner [47]. In this study, we have optimized targeting to human and murine cells and show that the liposomal incorporation of either 3 or 5 mol% GM3 led to strong and specific binding to CD169-expressing cells in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…While most Siglecs confer tolerogenic responses, the Siglec-1 (or CD169) receptor, expressed on splenic macrophages is of special interest for anti-tumor responses. These cells transferred antigen to cross-presenting cDC1s when targeted with liposomes coated with the Siglec-1 ligand GM3, conferring beneficial anti-tumor CD8+ T cell responses ( 115 ). FcR, which bind to the constant domains of antibodies can be targeted by coating liposomes with antibodies.…”
Section: Battling Cancer With DC Targeted Liposome Vaccinesmentioning
confidence: 99%
“…The authors used the natural ligands of CD169, gangliosides, as targeting ligands and constructed liposomal vaccine carriers to deliver TAs. Through targeted co-delivery of TA and TLR ligand to CD169 + monocyte-derived DCs and AXL + CD169 + DCs, the ganglioside-liposomes induce robust cross-presentation and activation of TA-specific CD8 + T cells 66 . Rajpu et al engineered polymeric nanovaccines using inulin acetate (InAc) as the polymer material.…”
Section: Antigen Release and Presentationmentioning
confidence: 99%